ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA INDUSTRI MAKANAN RINGAN BONGGOLAN - Muhammad Dedy Sholahuddin; Arfida Boedirochminarni; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2019)
This study aims to analyze the income and level of household welfare of the Bonggolan Snack industry in Srowo Village, Sidayu Gresik District. This research is descriptive quantitative, based on the results of the analysis of income and welfare levels of the snack food industry household in Srowo Village, Sidayu District, Gresik Regency, the average income in one month is IDR 21,412,500 / month with the production cost spent of IDR 16. 426,364 / month and earned a profit of IDR 4,986,136. In the calculation of welfare, the welfare level of the bulging industrial household in Srowo Village does not exist for the welfare level of KS I and KS II, but at the welfare level III and III plus. At the welfare level III there are 26 people with a percentage of 87% and at the welfare level III plus there are 4 people with a percentage of 13%. at the level of welfare in this study using a benchmark according to BKKBN, namely the indicators KS I, KS II, KS III, and KS III plus.